2011
DOI: 10.1038/onc.2011.523
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-520e suppresses growth of hepatoma cells by targeting the NF-κB-inducing kinase (NIK)

Abstract: MicroRNAs (miRNAs) are small, non-coding RNAs that can act as oncogenes or tumor suppressor genes in human cancer. Emerging evidence indicates that deregulation of miRNAs contributes to the hepatocarcinogenesis. In the present study, we demonstrated that the levels of miR-520e were dramatically decreased in examined hepatoma cell lines and clinical hepatocellular carcinoma (HCC) tissues. Moreover, we found that DNA hypermethylation in the upstream region of miR-520e resulted in the downregulation of miR-520e. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
85
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(88 citation statements)
references
References 45 publications
0
85
0
3
Order By: Relevance
“…The expression of miR-520e showed a tendency for increased values in the urine of the invasive tumour group compared with the controls. The findings of Zhang et al (31) suggest that miR-520e may be a tumour-suppressor miRNA in hepatocellular carcinomas since NF-κB-inducing kinase is one of the direct target genes of miR-520e. Further studies with a large sample size will confirm this tendency.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of miR-520e showed a tendency for increased values in the urine of the invasive tumour group compared with the controls. The findings of Zhang et al (31) suggest that miR-520e may be a tumour-suppressor miRNA in hepatocellular carcinomas since NF-κB-inducing kinase is one of the direct target genes of miR-520e. Further studies with a large sample size will confirm this tendency.…”
Section: Discussionmentioning
confidence: 99%
“…For mature miR-506 detection, total RNA was polyadenylated by poly(A) polymerase (Ambion, Austin, TX, USA) as described previously [8] . Reverse transcription was performed using poly(A)-tailed total RNA and reverse transcription primer with ImPro-II Reverse Transcriptase (Promega, Madison, WI, USA) according to the manufacturer's instructions.…”
Section: Cell Transfectionmentioning
confidence: 99%
“…Many studies have emphasized the causal links between miRNA deregulation and cancer development. Our laboratory has reported that miR-520e (or miR-205) suppresses the growth of hepatoma cells through the targeting of NF-kB-inducing kinase (NIK) mRNA (or hepatitis B virus X protein mRNA) [8,9] . Recently, it has been reported that miR-506 inhibits epithelial mesenchymal transition (EMT) in ovarian cancer and breast cancer [10,11] .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that dysfunction of miRNAs contributes to breast cancer development (11,14). Zhang et al reported that microRNA-520e (miR-520e) was associated with hepatocarcinogenesis (19); however, the biological significance of miR-520e in breast cancer remains largely unknown. The present study demonstrated that miR-520e is upregulated in breast cancer tissues and promotes proliferation, invasion and migration, and inhibits the apoptosis of cancer cells.…”
Section: Introductionmentioning
confidence: 99%